Safety of the evacuation process in commercial rooms - Barański, Mariusz; Brzezińska, Dorota (Instal, 2020)
The article presents the results of modeling the development of fire and evacuation in a commercial room in a situation of large numbers of people. The conducted research consisted in determining the required and available safe egress time in several selected variants, taking into account the number, width and location of emergency exits from the room, as well as the number of people in the room. Based on the obtained results, it was confirmed that providing the parameters of the emergency passage and emergency exits in the commercial room in accordance with the technical conditions does not ensure an adequate level of safety. It has been shown that it is necessary to equip the facility with additional fire protection devices to limit the development of fire, the spread of hot and toxic smoke, and to better organize the evacuation process.